DISCOVERY LEARNING MODEL IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS - Gita Ramadani (Journal of Quality Islamic Education Research, 2025)
This journal discusses the use of the discovery learning model in Islamic Religious Education subjects. This study uses qualitative research through a library research approach. This model was chosen because of its flexibility in all the materials taught. The purpose of this study is to develop students' understanding of Islamic teachings and 21st century skills. The implementation of the discovery learning model provides a positive contribution to the development of students' skills and understanding. This model is a reference for teachers in designing effective and relevant learning in Islamic Religious Education.